POVIDONE-IODINE IN EXPERIMENTAL PERITONEAL HYDATIDOSIS - GOKCE, O; GOKCE, C; YILMAZ, M; HUSEYINOGLU, K; GUNEL, S (Blackwell Science Ltd, 1991)
The effect of polyvinylpyrrolidone-iodine (PVP-I) on experimental peritoneal hydatidosis was evaluated in this randomized blind controlled study. Seventy-five white, 3-month-old rats were subjected to laparotomy. After the intraperitoneal inoculation of viable scolices, the rats were randomly divided into three groups. Their peritoneal cavities were irrigated with either 1 per cent PVP-I solution (the PVP-I group), hypertonic saline (the HS group) or Ringer's lactate (the control group). Each group was assigned a separate code number; observers blind to the meaning of the code numbers noted all findings during a period of 4 months, after which the rats were killed to allow assessment of the abdominal cavity. The results were decoded after the statistical analyses were completed. The incidence of peritoneal cysts was found to be lower (8.7 per cent) in the PVP-I group compared with the HS (50 per cent) and control (90.9 per cent) groups; the mean number of hydatid cysts per animal was also lower in the PVP-I group compared with the other two groups. We conclude that the scolicidal activity of PVP-I is significantly higher than that of hypertonic saline and that it can be employed as a prophylactic agent against peritoneal hydatidosis.
Keywords: Surgical-Treatment; Disease; Liver; Echinococcosis; Complications; Irrigation; Toxicity